Approach to String-Like Pulse in Traditional East Asian Medicine by Ultrasound device - PARK Jeongbin, Soung Hyebin, JUNG Sangsun, SONG Jichung, (International Journal of Advanced Science and Technology, 2020)
Pulse diagnosis is one of the most fundamental and important diagnostics in traditional Korean medicine. Pulse condition is difficult to master, because of writing only by text in the past. Although researches and machines for objectification of pulse have been developed in these days, it is hard to master pulse condition yet. Pulses are defined by several aspects; such as pulse location(superficial and deep pulse), pulse rate(slow and rapid pulse), pulse length(long and short pulse), pulse strength(forceful and forceless), pulse smoothness(stagnant and smooth pulse), pulse tension(tension and relaxation), pulse thickness(string and enlarged pulse) and so on. Some of them we could express pulse form visibly, especially with string pulse and enlarged pulse because those have pulse shape like thick or thin. So we study pulse actualization with especially string pulse out of two. Also we focused on what the place of inch-bar-cubit is just on the radial artery. That means that measuring the change of radial artery thickness by some given conditions would show the actualized pulse definition with visual evidence not only with practitioners’ fingertip sensation.Methods: The string pulse is straight and narrowed like a string with a bow which is referred to traditional medical classic such as Nanjing, Maijing and other text for diagnosis. It could be explained by thickness of radial artery. According to medical classics, what string pulse mainly represents fatigue on human body. That means if somebody had fatigue on his or her body the pulse would be changed into string pulse from normal. Therefore, we check thickness of radial artery by ultrasound after causing artificial fatigue. 1) Measure the thickness of radial artery after 30 min break for making sure the normal pulse. 2) Make subject to grab handgrip for 1 min to make him or her in fatigue stage. 3) Measure again the thickness of radial artery. 4) Compare the values of radial artery thickness between before and after grabbingResults: After causing artificial fatigue, thickness of radial artery is decreased after the experiment. The thickness of RA of Subject A had been changed from 1.8mm to 1.6mm and Subject B from 2.0mm to 1.6mm.Conclusion: This change from experiments above shows that RA was influenced by even short term stimulation like grabbing handgrip. Also that explains that just like artificial fatigue could make string pulse condition, real fatigue would cause making string pulse on his or her wrist. So with that way, we could define or diagnose patients’ fatigue status with ultra sound results not only with oral explanation. In this study, we verify that string pulse condition could be actualized with ultrasound. As the first study for actualization only with string pulse, there is more need to experiment actualizing with other pulses.